Femtosecond intersubband dynamics of electrons in AlGaN/GaN-based high-electron-mobility transistors - Wang, Z.; Reimann, K.; Woerner, M.; Elsaesser, T.; Hofstetter, Daniel; Hwang, Jeff; Schaff, William J.; Eastman, Lester F. (My University, 2004)
Ultrafast electron dynamics in the inversion layer of an AlGaN/GaN transistor is studied in pump–probe experiments with 50 fs mid-infrared pulses. Two-colour pump–probe measurements show an instantaneous transmission increase for all spectral positions of the probe, which demonstrates that homogeneous broadening is an important contribution to the total linewidth in this material. We observe the maximum of the induced transmission change around 5 µm. This large Stokes shift might be caused by the extremely large electron–LO-phonon scattering rate.